A systematic review on social media echo chambers and political persuasion - Latupeirissa, Jonathan Jacob Paul; Cistadewi, Ni Made Wulan (Jurnal Studi Komunikasi, 2025)
This study addresses the increasing concern surrounding social media echo chambers and their impact on political discourse. While echo chambers are often framed as a universal phenomenon, reinforcing existing beliefs and limiting exposure to diverse perspectives, this review recognises that cultural, political, and infrastructural factors significantly influence how echo chambers form and operate in different contexts. Factors such as social media regulation, censorship policies, and linguistic diversity play crucial roles in shaping these dynamics beyond Western settings. This research aimed to undercover how algorithmic curation, selective exposure, and socio-political contexts shape social media echo chambers and political persuasion. It seeks to analyse cognitive and affective factors reinforcing partisan beliefs and misinformation, evaluate cross-cultural differences, and identify strategies to foster cross-partisan dialogue and democratic engagement. This study employed a Systematic Literature Review approach, drawing upon the Scopus Database to evaluate existing studies, identify key themes, and highlight areas for future research. The PRISMA guidelines were followed to ensure methodological rigour and transparency. Key findings reveal that algorithmic curation and selective exposure, combined with the sharing of emotionally charged content, systematically limit exposure to contradicting evidence, allowing disinformation to thrive unchecked within insular communities. Furthermore, affective polarisation intensifies partisan hostility, making users more receptive to accepting false or exaggerated claims. Intensifying partisan hostility creates an emotional environment where individuals become more likely to accept false or exaggerated claims aligned with their political identity. The study recommends that future research should focus on exploring the psychological drivers of echo chamber participation, developing strategies for mitigating the impact of disinformation, and examining the effectiveness of interventions aimed at promoting critical thinking and media literacy.